2020
DOI: 10.3390/su12135456
|View full text |Cite
|
Sign up to set email alerts
|

Maltose and Totally Impermeable Film Enhanced Suppression of Anaerobic Soil Disinfestation on Soilborne Pathogens and Increased Strawberry Yield

Abstract: Anaerobic soil disinfestation (ASD) is widely used to control soilborne diseases in organic crop production. The effect of ASD used different sealed films on soilborne pathogens and strawberry growth was evaluated in two laboratory studies and two field trials. Under maltose as carbon sources, 28 °C temperature and 30% of soil moisture optimal conditions ASD decreased Fusarium spp. and Phytophthora spp. by 100%. ASD used maltose as an organic amendment and sealed with totally impermeable film (TIF) obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Overbeek et al [26] found that ASD reduced the abundance of Ralstonia solanacearum in soil by more than 99.4%, and that such reductions also reduced bacterial wilt incidence. Our previous research had shown that ASD could be applied in pre-plant fumigation to control strawberry soil-borne pests, strengthen soil fertility, improve crop yield, and increase growers' income [13,27]. In this experiment, we found that Fusarium and Phytophthora species in Trials I and II were significantly reduced by as much as 98.6% 10 d after disinfestation.…”
Section: Effects Of Asd On Soil Pathogensmentioning
confidence: 63%
See 1 more Smart Citation
“…Overbeek et al [26] found that ASD reduced the abundance of Ralstonia solanacearum in soil by more than 99.4%, and that such reductions also reduced bacterial wilt incidence. Our previous research had shown that ASD could be applied in pre-plant fumigation to control strawberry soil-borne pests, strengthen soil fertility, improve crop yield, and increase growers' income [13,27]. In this experiment, we found that Fusarium and Phytophthora species in Trials I and II were significantly reduced by as much as 98.6% 10 d after disinfestation.…”
Section: Effects Of Asd On Soil Pathogensmentioning
confidence: 63%
“…Previous research has reported that anaerobic conditions generated by incorporating broccoli and weed materials into the soil significantly reduced the number of Fusarium oxysporum and Verticillium dahlia pathogens [12]. Song et al [13] generated anaerobic conditions using maltose that reduced soil pathogens and increased strawberry yield. The effect of ASD is determined mostly by the organic material used as the carbon source, the soil's properties, the availability of water, and the size of the field [14].…”
Section: Introductionmentioning
confidence: 99%
“…and Phytophthora spp. was recorded as Colony‐Forming Units (CFU) g −1 soil to quantify the effect of soil fumigation on soil‐borne pathogens according to previous studies 26–28 …”
Section: Methodsmentioning
confidence: 99%
“…was recorded as Colony-Forming Units (CFU) g −1 soil to quantify the effect of soil fumigation on soil-borne pathogens according to previous studies. [26][27][28] The root-knot nematode (RKN, Meloidogyne spp.) population was extracted following previous method.…”
Section: Determination Of Pest-control Effectmentioning
confidence: 99%
“…However, thorough studies are necessary targeting the tropical region since there is a severe information gap. One major limitation in ASD is the cost associated with the use of plastic/impermeable sheets, and it is estimated that ASD costs more than chemical fumigation [ 105 , 106 ]. In addition, labour cost and non-biodegradability of polyethylene are serious issues.…”
Section: Challenges and Potentials Of Asd As A Game Changer In Thementioning
confidence: 99%